1998
DOI: 10.1002/(sici)1096-9861(19980420)393:4<505::aid-cne9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Visuotopic organisation and neuronal response selectivity for direction of motion in visual areas of the caudal temporal lobe of the marmoset monkey (Callithrix jacchus): Middle temporal area, middle temporal crescent, and surrounding cortex

Abstract: On the basis of extracellular recordings in marmoset monkeys, we report on the organisation of the middle temporal area (MT) and the surrounding middle temporal crescent (MTc). Area MT is approximately 5-mm long and 2-mm wide, whereas the MTc forms a crescent-shaped band of cortex 1-mm wide. Neurones in area MT form a first-order representation of the contralateral hemifield, whereas those in the MTc form a second-order representation with a field discontinuity near the horizontal meridian. The representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 85 publications
9
106
0
Order By: Relevance
“…In a previous study (Rosa and Elston, 1998), we demonstrated that area MT in normal marmosets has a simple visuotopic organization that is remarkably constant among individuals. As demonstrated in Figure 3, at any anteroposterior level, a dorsoventral movement of the electrode results in a regular change in the polar angle of receptive field centers, which gradually move from the lower quadrant toward the upper quadrant.…”
Section: Receptive Field Mappingmentioning
confidence: 73%
See 4 more Smart Citations
“…In a previous study (Rosa and Elston, 1998), we demonstrated that area MT in normal marmosets has a simple visuotopic organization that is remarkably constant among individuals. As demonstrated in Figure 3, at any anteroposterior level, a dorsoventral movement of the electrode results in a regular change in the polar angle of receptive field centers, which gradually move from the lower quadrant toward the upper quadrant.…”
Section: Receptive Field Mappingmentioning
confidence: 73%
“…In the right diagram, receptive fields from the same rostrocaudal level are connected in sequences that correspond to sites progressing from dorsal to caudal in the cortex (e.g., 1-8, 9 -15, etc.). For clarity, not every recording site or receptive field obtained in this case is illustrated (Rosa and Elston, 1998). spared region was confirmed by both the presence of responsive V2 cells covering that part of the visual field and histological reconstruction].…”
Section: Receptive Field Mappingmentioning
confidence: 81%
See 3 more Smart Citations